Governmental Logics in Commercialised Planning Practices. The Case of Local Authority Pre-Application Negotiations in the English Planning System. (1st January 2022) - Parker, Gavin; Dobson, Mark; Lynn, Tessa
ABSTRACT: The paper provides an empirical review of a widely used tool in the English planning system – pre-application discussions ('pre-apps') and a theoretical exposition of governmental 'logics' that underpin neoliberal-informed planning reforms. We present five logic frames of growth, efficiency, commercialisation, participation and quality, and apply these to pre-application negotiation practice, to highlight how Local Planning Authorities (LPAs) are faced with the challenge of reconciling a complex of multiple and often competing aims that appear irreconcilable in practice. We highlight that whilst 'ordinary' planning tools such as pre-apps may appear mundane, they can provide valuable instantiations where logics collide.